The feasibility and acceptability of using a novel wrist worn cueing device to self-manage drooling problems in people with Parkinson's disease: A pilot study. (July 2019) - McNaney, Roisin; Miller, Nick; Vines, John; Olivier, Patrick; Ladha, Karim; Jackson, Daniel; Walker, Richard
Introduction: Daytime drooling is experienced by around 50% of Parkinson's patients, who fail to swallow saliva in sufficient volume or regularity, despite normal production. This research explored the feasibility and acceptability of using a cueing device, to improve drooling. Methods: During a four-week intervention, 28 participants were asked to use a cueing device for 1 h per day. During this time, the device vibrated once-per-minute, reminding the participant to swallow their saliva. A daily diary was used to collect self-report around swallowing severity, frequency, and duration. This was filled out by participants for one week before, four weeks during and for one week immediately after intervention. Diaries were also collected for one week during a follow up, carried out four weeks after intervention finished. Results: Participants self-reported benefits in drooling severity ( p  = 0.031), frequency ( p  ≤ 0.001), and duration ( p  = 0.001) after using the device. Improvements were maintained at follow up. Twenty-two participants explicitly reported a positive benefit to their drooling during exit interview. All felt the intervention and device were acceptable and usable. Conclusions: Using a cueing device for one month had perceived benefit to drooling severity, frequency and duration in patients with Parkinson's. Participants accepted the device and treatment protocol.